Perbandingan Metode Penentuan Intensitas Curah Hujan (Studi Kasus: Kawasan Wilayah Sukarame Bandar Lampung) - Yanti, Cristi; Herison, Ahmad; Zakaria, Ahmad; Romdania, Yuda (Universitas Lampung, 2023)
One of the main factors causing flooding in an urban area is rainfall intensity. Perhaps this research has been widely discussed in other studies, but this research was conducted in an area with rainfall characteristics that are different from other areas, so this research is expected to provide further information for flood management and water structure design in related areas. The purpose of the research is to obtain and compare rain intensity methods in order to select a method that is suitable for rainfall characteristics in the sukarame area. The short-term intensity calculation method uses the Mononobe method because this method only requires maximum daily rainfall data. The calculation of rain intensity approach uses Talbot and Sherman methods to find the appropriate rain intensity method. The results showed that high-intensity rain lasts for a short duration. From the comparison results, different rain intensity analysis results were obtained, this may be due to the use of different settings from each method. It is concluded that the Mononobe method with the Sherman equation is most suitable for rainfall characteristics. Key words : Rainfall Intensity, Mononobe, Talbot, Sherman, IDF Curve.